Extracellular detection of delayed afterdepolarization of cardiac fibers using signal averaging technique - Xie Jing-Tian; Lowell Tasha K.; Yuan Chun-Su (Acta Pharmacologica Sinica; Vol 21, No 11 (November 2000): Acta Pharmacologica Sinica, 2016)
"AIM: To detect delayed after depolarizations (DAD) in extracellular electrograms using signal averaging technique. METHODS: DAD were induced by acetylstrophanthidin (0.25 mumol.L-1, n = 9) and resibufogenin (0.52 mumol.L-1, n = 5) in sheep cardiac Purkinje fibers. Intracellular voltage was recorded with a conventional microelectrode, and simultaneous extracellular electrograms were recorded differentially from widely spaced electrodes placed in the tissue bath. Noise of electrograms was reduced using signal averaging technique. RESULTS: Acetylstrophanthidin and resibufogenin both induced DAD in the intracellular recording and extracellular DAD (DAD-E) in the extracellular electrogram in sheep heart Purkinje fibers. Acetylstrophanthidin and resibufogenin induced typical changes in the action potential including decrease in action potential amplitude, resting potential, maximum diastolic potential, and action potential duration. Similar shortening occurred in the ""Q-T interval"" recorded by the extracellular electrogram. With either acetylstrophanthidin or resibufogenin, shortening of stimulation cycle length from 990 ms to 690 ms reduced the coupling interval between action potential upstroke and peak voltage of the DAD (P < 0.01), and the coupling interval between the ""QRS"" and DAD-E recorded extracellularly (P < 0.01). CONCLUSION: DAD can be detected using the extracellular electrograms combined with the high resolution, signal averaging technique."